Urinary proteomics using capillary electrophoresis coupled to mass spectrometry for diagnosis and prognosis in kidney diseases - Magalhães, Pedro (Curr Opin Nephrol Hypertens, 2016)
PURPOSE OF REVIEW: Urine is the most useful of body fluids for biomarker research. Therefore, we have focused on urinary proteomics, using capillary electrophoresis coupled to mass spectrometry (CE-MS), to investigate kidney disease in recent years. RECENT FINDINGS: Several urinary proteomics studies for the detection of various kidney diseases have indicated the potential of this approach aimed at diagnostic and prognostic assessment. Urinary protein biomarkers such as collagen fragments, serum albumin, alpha-1-antitrypsin, and uromodulin can help to explain the processes involved during disease progression. SUMMARY: Urinary proteomics has been used in several studies, in order to identify and validate biomarkers associated with different kidney diseases. These biomarkers, with improved sensitivity and specificity when compared to the current gold standards, provide a significant alternative for diagnosis and prognosis, as well as improving clinic decision making.